2008
DOI: 10.3354/ab00029
|View full text |Cite
|
Sign up to set email alerts
|

Sources of otolith carbonate: experimental determination of carbon incorporation rates from water and metabolic CO2, and their diel variations

Abstract: Although carbon isotopes in fish otoliths are widely utilized to obtain information on environmental records, uncertainty regarding the sources of otolith carbonate, either from fish diet or ambient water, limits detailed determinations. The present study experimentally determined absolute incorporation rates of carbon derived from 2 sources, metabolic CO 2 and ambient water, into otoliths using goldfish under controlled conditions. In addition, the proportions of the 2 sources in otolith daily increments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…The results of this experiment and the experiments of others clearly demonstrate some influence of metabolically derived carbon on otolith δ 13 C value (Kalish 1991, Radtke et al 1998b, Schwarcz et al 1998, Høie et al 2003, Solomon et al 2006, Tohse & Mugiya 2008. But, in order to properly interpret carbon stable isotope results for use in ecological studies, it is necessary to know the relative contribution of DIC and diet to the observed otolith δ 13 C value.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The results of this experiment and the experiments of others clearly demonstrate some influence of metabolically derived carbon on otolith δ 13 C value (Kalish 1991, Radtke et al 1998b, Schwarcz et al 1998, Høie et al 2003, Solomon et al 2006, Tohse & Mugiya 2008. But, in order to properly interpret carbon stable isotope results for use in ecological studies, it is necessary to know the relative contribution of DIC and diet to the observed otolith δ 13 C value.…”
Section: Discussionsupporting
confidence: 53%
“…But, in order to properly interpret carbon stable isotope results for use in ecological studies, it is necessary to know the relative contribution of DIC and diet to the observed otolith δ 13 C value. To that end, studies with various fish species have demonstrated a dietary contribution ranging from 17 to 35% (Kalish 1991, Høie et al 2003, Solomon et al 2006, Tohse & Mugiya 2008. Solomon et al (2006), in a detailed experimental study on rainbow trout, estimated fractionation factors associated with otolith formation by manipulating the ambient water DIC δ 13 C and the dietary δ 13 C and, subsequently, by measuring the δ 13 C of the otolith, the endo lymph DIC, and the blood DIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Solomon et al (2006) reported that in Rainbow Trout, Oncorhynchus mykiss greater than 80% of otolith δ 13 C was derived from DIC in ambient seawater, while 17% was metabolically derived. In addition, Tohse and Mugiya (2008) determined that in Goldfish, Carassius auratus 75% of δ 13 C in otolith carbonates is derived from DIC in ambient seawater with the remainder (25%) derived from metabolic sources. There appears to be a large amount of variation among species in the proportion of metabolically derived δ 13 C in otoliths ranging from 5 to 40% and concomitantly in that derived from DIC in ambient seawater (Solomon et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Organic tissue carbon has a much more negative d 13 C vPDB value, typically ranging between ca 230‰ and 220‰. Consequently, while there is some evidence for isotopic fractionation of carbon during membrane transfer [61], the isotopic composition of carbon in biomineral carbonates in heterotrophic organisms represents a weighted average between the isotopic compositions of the dissolved inorganic and metabolic carbon sources, and increasing metabolic rates will drive biomineral carbon isotopes towards more negative values [59][60][61][62].…”
Section: Metabolic Ratementioning
confidence: 99%